2021
DOI: 10.1210/jendso/bvab084
|View full text |Cite
|
Sign up to set email alerts
|

Neprilysin Inhibition Increases Glucagon Levels in Humans and Mice With Potential Effects on Amino Acid Metabolism

Abstract: Context Inhibitors of the protease neprilysin (NEP) are used for treating heart failure, but are also linked to improvements in metabolism. NEP may cleave proglucagon-derived peptides, including the glucose and amino acid (AA)-regulating hormone glucagon. Studies investigating NEP inhibition on glucagon metabolism are warranted. Objective To investigate whether NEP inhibition increases glucagon levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…We have previously showed that neprilysin cleaves glucagon both in vivo in healthy individuals, and in in vitro experiments. 13,19 While considering the powerful effects of glucagon on hepatic glycogenolysis and gluconeogenesis, it seems probable that the hyperglucagonaemia found after neprilysin inhibition may explain the impairment in glucose tolerance of patients with type 2 diabetes in our study. The effect on glucose concentrations by sacubitril/valsartan could in theory also be explained by increased activity of the sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…We have previously showed that neprilysin cleaves glucagon both in vivo in healthy individuals, and in in vitro experiments. 13,19 While considering the powerful effects of glucagon on hepatic glycogenolysis and gluconeogenesis, it seems probable that the hyperglucagonaemia found after neprilysin inhibition may explain the impairment in glucose tolerance of patients with type 2 diabetes in our study. The effect on glucose concentrations by sacubitril/valsartan could in theory also be explained by increased activity of the sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 71%
“…Neprilysin activity was measured using a previously described in-house assay. 13 Insulin, C-peptide, fatty acids and triglycerides were analysed using Roche COBAS 8000 system. Clot activator tubes were left at room temperature to coagulate for 30 min, whereas EDTA-tubes were placed on ice immediately until centrifuged at 4 C (2000 g for 10 min).…”
Section: Sample Collection and Biochemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, heart failure is associated with insulin resistance ( 66 ) and increased sympathetic nerve activity ( 67 ), the latter known to inhibit insulin secretion and stimulate both hepatic gluconeogenesis and glycogenolysis ( 68 ). Interestingly, treatment of obese hypertensive patients with sacubitril/valsartan for 8 weeks was associated with decreased levels of epinephrine and improved insulin sensitivity in one study ( 4 ), but no effect on fasting glucose levels in a more recent study ( 69 ). To better clarify the role of heart failure in the glycemic effects of sacubitril/valsartan and its components, further studies in a mouse model that recapitulates the clinical features of heart failure in the setting of diabetes would be valuable.…”
Section: Discussionmentioning
confidence: 98%
“…Sacubitril/valsartan also significantly lowered plasma triglycerides in HFpEF patients, especially in those with higher baseline triglycerides, while modestly increasing low-and high-density lipoprotein cholesterols [33]. Moreover, one-time sacubitril/valsartan elevated the post-prandial glucagon in healthy individuals, while over 8 weeks, the drug increased fasting glucagon in obese hypertensive individuals, without changes in fasting glucose or amino acids [34], suggesting a potential role of ARNI in modulating dyslipidemia and metabolic diseases (Figure 3).…”
Section: Other Cardiovascular Diseasesmentioning
confidence: 89%